2012
DOI: 10.1007/s00018-012-1179-y
|View full text |Cite
|
Sign up to set email alerts
|

Surface display of a single-domain antibody library on Gram-positive bacteria

Abstract: Combinatorial protein engineering for selection of proteins with novel functions, such as enzymes and affinity reagents, is an important tool in biotechnology, drug discovery, and other biochemical fields. Bacterial display is an emerging technology for isolation of new affinity proteins from such combinatorial libraries. Cells have certain properties that are attractive for directed evolution purposes, in particular the option to use quantitative flow-cytometric cell sorting for selection of binders. Here, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 42 publications
0
33
1
Order By: Relevance
“…It has previously been demonstrated that staphylococcal cell surface display in combination with fluorescenceactivated cell sorting (FACS) is well suited for combinatorial affinity maturation efforts, since it allows for high precision affinity discrimination between binders [35][36][37][38]. Recently, the method was used for affinity maturation of a HER3-specific Affibody, and generated binders with picomolar affinities [39].…”
Section: A Truncated and Dimeric Format Of An Affibody Library On Bacmentioning
confidence: 99%
See 1 more Smart Citation
“…It has previously been demonstrated that staphylococcal cell surface display in combination with fluorescenceactivated cell sorting (FACS) is well suited for combinatorial affinity maturation efforts, since it allows for high precision affinity discrimination between binders [35][36][37][38]. Recently, the method was used for affinity maturation of a HER3-specific Affibody, and generated binders with picomolar affinities [39].…”
Section: A Truncated and Dimeric Format Of An Affibody Library On Bacmentioning
confidence: 99%
“…It has been shown that there is a correlation between the affinity of peripherally-administered Ab-specific agents and the efflux of Ab from the brain to the serum [29]. As levels of Ab peptides in the blood are low (subnanomolar) [30][31][32][33][34], it is probably critical to use capturing-agents of high affinity for such applications.It has previously been demonstrated that staphylococcal cell surface display in combination with fluorescenceactivated cell sorting (FACS) is well suited for combinatorial affinity maturation efforts, since it allows for high precision affinity discrimination between binders [35][36][37][38]. Recently, the method was used for affinity maturation of a HER3-specific Affibody, and generated binders with picomolar affinities [39].…”
mentioning
confidence: 99%
“…After two consecutive rounds of phage display and panning, we obtained four unique VHHs specific for influenza virus. Three additional VHHs specific for influenza virus were then obtained by selection using staphylococcal surface expression (38). All seven VHHs were equipped with a C-terminal sortase motif (41,42) followed by a 6ϫHis tag, expressed in bacteria, and purified on a Ni-NTA affinity matrix followed by size exclusion chromatography.…”
Section: Resultsmentioning
confidence: 99%
“…The second method utilized recombinant influenza virus protein with a C-terminal sortase motif expressed in 293T cells, biotinylated, and immobilized on streptavidin beads. A third method utilized a Staphylococcus aureus display platform, based on a strategy developed for Staphylococcus carnosus (38), which will be described in detail elsewhere.…”
Section: Methodsmentioning
confidence: 99%
“…In all cases, antigen-specific nanobodies are retrieved from these libraries by phage display or other selection protocols such as bacterial display [57], yeast display [58] or ribosome display [59]. Due to its robustness, the phage display method is the most often used one.…”
Section: Nanobodies Are Easy To Generate Select and Producementioning
confidence: 99%